1976
DOI: 10.1136/bmj.1.6012.753
|View full text |Cite
|
Sign up to set email alerts
|

Preventing the birth of infants with Down's syndrome: a cost-benefit analysis.

Abstract: SummaryThe costs and economic benefits of providing routine prenatal diagnosis of Down's syndrome with termination of affected pregnancies in older pregnant women in the west of Scotland were examined. The potential economic benefits would be greater than the costs for women aged 40 and over, probably about equal to costs for those aged 35 and over, but less than costs ifthe service were extended to women under 35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(29 citation statements)
references
References 4 publications
0
28
0
1
Order By: Relevance
“…Plusieurs auteurs ont estimé le ratio coût/efficacité des stratégies de dépistage fondées sur l'âge maternel, l'échographie et les marqueurs sériques [42][43][44][45]. Les résultats ont été calculés à partir d'une étude de cohorte réelle et ont exclu toutes les coûts directs ou indirects encourus après l'issue de la grossesse en cours.…”
Section: Discussionunclassified
“…Plusieurs auteurs ont estimé le ratio coût/efficacité des stratégies de dépistage fondées sur l'âge maternel, l'échographie et les marqueurs sériques [42][43][44][45]. Les résultats ont été calculés à partir d'une étude de cohorte réelle et ont exclu toutes les coûts directs ou indirects encourus après l'issue de la grossesse en cours.…”
Section: Discussionunclassified
“…An early example of a study which addressed this question is that by Hagard and Carter (1976) in which the costs and benefits of providing routine prenatal diagnosis of Down's syndrome in older pregnant women were examined. The authors measured benefits in terms of the costs of care averted from the detection and termination of affected fetuses.…”
Section: Economic Evaluation Of Amniocentesismentioning
confidence: 99%
“…For example, averted costs were used by Sadovnick and Baird (1 98 1) in an evaluation of amniocentesis to detect Down's syndrome and neural tube defects. The study adopted a narrower perspective than that by Hagard and Carter (1976) in that only costs to the provincial government were considered. Benefit:cost ratios were calculated for a number of maternal ages and it was concluded that amniocentesis should be offered to all women aged 34 years and above.…”
Section: Economic Evaluation Of Amniocentesismentioning
confidence: 99%
“…Firstly, this threshold was chosen because women at that age have an approximately equal risk for a procedure-related miscarriage and the chance to have a child with Down syndrome [8]. Secondly, the costs of prenatal invasive diagnostics are counterbalanced by the possible savings associated with the treatment of a child with Down syndrome [9]. Recent investigations pointed out that there is no age threshold below which prenatal diagnosis would be cost ineffective [10].…”
Section: Genetic Counseling and Prenatal Testingmentioning
confidence: 99%